2022
DOI: 10.1155/2022/9594798
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Wear Behavior of Aluminium Composites at Elevated Temperature

Abstract: The aerospace aluminium alloy AA7050 was reinforced with Al2O3 of average particle size 5 m in this study using the stir casting method. To eliminate surface imperfections, AA7050/Al2O3 composites with varied weight percentages (0, 2, 4, 6) were manufactured, and wear tests on composites were carried out utilizing a pin-on-disc apparatus that varied load, velocity, temperature, and weight %. The tensile and hardness tests were carried out at a high temperature. The inclusion of particles enhances wear resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…It was shown that as the ageing temperature increased, Ra decreased. The observed phenomenon can be explained by the decrease in frictional stress on micro MMCs and the decreasing tendency towards the formation of Built-Up Edges (BUEs) with increasing ageing temperatures [13]. Predominantly, samples that have been heat-treated had smoother surfaces than samples that had not, which are in line with research findings from other studies [14].…”
Section: Cutting Force and Rasupporting
confidence: 86%
See 2 more Smart Citations
“…It was shown that as the ageing temperature increased, Ra decreased. The observed phenomenon can be explained by the decrease in frictional stress on micro MMCs and the decreasing tendency towards the formation of Built-Up Edges (BUEs) with increasing ageing temperatures [13]. Predominantly, samples that have been heat-treated had smoother surfaces than samples that had not, which are in line with research findings from other studies [14].…”
Section: Cutting Force and Rasupporting
confidence: 86%
“…6. It has been observed that when the weight percentage of hard ceramic particles increases, the wear resistance of the MMCs also increases [13,14]. Nano particles in the metal matrix composites will greatly improve the wear resistance.…”
Section: Wear Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…In robot manipulators, the PSO method improves the optimization control utilized to regulate the DC motor parameter 14 . The sophisticated technique PSO mutation algorithm is utilized to address the industrial robot handler optimization problem 15 , 16 . The reverse dynamic control of the robot manipulator using fuzzy and PSO controllers is presented for checking the optimum problem 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in automotive and aerospace technology, the use of high-performance and lightweight structural components with the goal of lowering cost, energy consumption, and emissions is very difficult. But it can be achieved by using aluminium metal matrix nanocomposites that will be suitable for automotive and aerospace applications.Especially Al7075 reinforced with hybrid nano ceramic particles.It plays a vital role in development to satisfy modern industry and societal requirements [1], [2]. Because of their superior mechanical and wear properties over conventional materials, Al7075 metal matrix nanocomposites have created the interest of recent researchers in developing the required components in the automotive and aerospace fields.…”
Section: Introductionmentioning
confidence: 99%